2014
DOI: 10.4236/ijohns.2014.31010
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear and Vestibular Functional Study in Patients with Sudden Deafness and Lyme Disease

Abstract: Lyme disease (LD) and idiopathic sudden deafness (ISD) are supposed to be different diseases with different aetiologies. In an attempt to confirm this assumption, 10 patients with confirmed LD and 12 patients with ISD were consecutively included into the study. Further to the laboratory and audio logical investigation, a low frequency sound (LFS) stimulation on posturography was performed and evaluated. Patients with ISD had higher pure tone average (PTA) than patients with LD (PTA ISD/LD was 72 decibel (dB)/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…One of the most peculiar features of neuroborreliosis can manifest up to 1 year after a disseminated infection, as in this case report 2 . It is assumed that the pathogenetic mechanism of the SSNHL in Lyme disease is related both to an immunological reaction and to an angiopathic injury of the cochlea 17,21,22 . On the contrary, facial nerve involvement seems to be related only to an aspecific inflammatory process 19,23 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…One of the most peculiar features of neuroborreliosis can manifest up to 1 year after a disseminated infection, as in this case report 2 . It is assumed that the pathogenetic mechanism of the SSNHL in Lyme disease is related both to an immunological reaction and to an angiopathic injury of the cochlea 17,21,22 . On the contrary, facial nerve involvement seems to be related only to an aspecific inflammatory process 19,23 .…”
Section: Discussionmentioning
confidence: 69%
“…2 It is assumed that the pathogenetic mechanism of the SSNHL in Lyme disease is related both to an immunological reaction and to an angiopathic injury of the cochlea. 17,21,22 On the contrary, facial nerve involvement seems to be related only to an aspecific inflammatory process. 19,23 According to the current literature, the diagnosis of neuroborreliosis requires meeting the following criteria: neurologic signs compatible with Lyme neuroborreliosis, CSF pleocytosis (>5 cells × 10 9 L), intrathecal production of specific antibodies (B. burgdoferi IgM and/or IgG).…”
Section: Discussionmentioning
confidence: 99%
“…Very often, the symptoms coincided with hearing loss and tinnitus, which implies the location of the disease being within the inner ear. Selmani et al [18] confirmed the occurrence of vertigo in five out of eight patients with LD (62.5%), comparing the results with a group of patients with idiopathic sudden deafness. Ishizaki et al [19] suggest that vertigo can be the predominant symptom in patients with confirmed LD, its symptoms resembling neuronitis vestibularis in the acute stage.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, Selmani et al suggest that hearing loss in LD could be a result of inflammation impact by an immunological reaction in the cochlea by BB infection. The first manifestation of this reaction is an elevated level of IgM [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Otolaryngological manifestation of LD included different symptoms such as sore throat, otalgia, cervical adenopathy, facial nerve palsy tinnitus, vertigo, and hearing loss. Many authors have been mentioned the occurrence of hearing loss in LD patients [ 3 , 9 , 10 , 11 ], but only a few reports in the literature concern sudden loss of hearing cases [ 9 , 12 , 13 , 14 ]. The aim of the study was to assess the prevalence of SSNHL among the hospitalized patients; furthermore, it includes an attempt to answer the question of whether the Borrelia burgdorferi infection that causes Lyme disease may be the reason for SSNHL.…”
Section: Introductionmentioning
confidence: 99%